A novel dynamic pseudo[1]rotaxane based on a mono-biotin-functionalized pillar[5]arene1. Issue 9 (13th September 2015) - Wu, Xuan; Ni, Mengfei; Xia, Wei; Hu, Xiao-Yu; Wang, Leyong
<x xml:space="preserve">Abstract</x> A stable pillar[5]arene-based pseudo[1]rotaxane P1′ was synthesized by the click reaction, which exhibited a dynamic slow disassembly process upon adding a strong-polar solvent or competitive guest. Moreover, this dynamic behavior might be used as a switch to turn on or off the bioactivity of the biotin moiety in aqueous solution.